2022
DOI: 10.3389/fncel.2022.954807
|View full text |Cite
|
Sign up to set email alerts
|

Maternal lead exposure induces sex-dependent cerebellar glial alterations and repetitive behaviors

Abstract: Lead (Pb) is one of the most prevalent heavy metals we encounter daily. Although there are many reports regarding their toxic effects on humans, the effects of exposure to low lead concentrations throughout the pregnancy period on the offspring are not fully elucidated yet. This study aimed to investigate the cellular mechanisms that occur in response to lead exposure. To this end, we administered lead-containing water to pregnant mice from the day of conception till delivery or till day 28 postnatally. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…According to a recent report, only male mice show repetitive behavioral and glial changes in their offspring after exposure to low lead concentrations during pregnancy. The expression patterns of glia-related molecules vary according to gender differences [72]. Therefore, it is necessary to include both males and females in ADHD animal models.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent report, only male mice show repetitive behavioral and glial changes in their offspring after exposure to low lead concentrations during pregnancy. The expression patterns of glia-related molecules vary according to gender differences [72]. Therefore, it is necessary to include both males and females in ADHD animal models.…”
Section: Discussionmentioning
confidence: 99%
“…For example, high expression levels of microglia markers were observed in males ( Werling et al, 2016 ). In a model of exposure to low lead concentrations during pregnancy, increased glial cells proliferation in the cerebellum of lead-exposed male pups led to an increased incidence of autism-like behavior, suggesting that sex-dependent glial cells influence the incidence of autism-like behavior ( Choi et al, 2022 ). Further evidence regarding sex-specific differences in microglia could be found.…”
Section: Microglia Contribute To Neuroinflammation In Asd By Releasin...mentioning
confidence: 99%
“…Previous studies have reported reductions in GABAergic interneurons and transmission in mouse models of ASD ( Kim et al, 2020 ). Furthermore, in a model of maternal lead exposure, astrogliosis was able to prevent behavioral changes by ensuring high GABA levels ( Choi et al, 2022 ). Meanwhile, inhibition of abnormally elevated GABAergic synaptic transmission in the hippocampal CA1 region has been shown to restore E/I balance and rescue autism-like behavior ( Chen et al, 2022 ).…”
Section: Neurotransmitter and Ion Channels Expressed By Astrocytes Fa...mentioning
confidence: 99%